Assessment of drinking water and wastewater quality in selected dairy cattle farms from Malaysia - Abdullah Jesse, Faez Firdaus; Naidu, Nagachandra Rao Gopi; Wan Johari, Wan Lutfi; Lim, Eric Teik Chung; Thlama, Bura Paul; Mohd Lila, Mohd Azmi; Haron, Abd Wahid (Scopus, 2022)
There is a paucity of published research information on the quality of water used in the Malaysian ruminant livestock production system. Also, there are growing concerns about the sanitation standards of ruminant farms as it affects the management of wastewater in Malaysia. This study was designed to compile preliminary data on the drinking water and wastewater quality in designated dairy cattle farms in the Klang Valley. Seven dairy farms were randomly selected and visited to collect samples of drinking and wastewater for laboratory analysis. The water samples were analyzed to determine dissolved oxygen (DO), pH, salinity, electrical conductivity, turbidity, biological oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS), total dissolved solids (TDS), ammoniacal nitrogen, nitrate, phosphates, total coliform count, iron, and magnesium content. The means of various parameters were compared with the National Water Quality Standards (NWQS) to determine the appropriate classification. We further streamlined the rating of water quality into three broad categories, namely, good (Class I and II), moderate (Class III) and unsatisfactory (Class IV and V). Analysis of drinking water revealed 1(14.29%), 2 (28.57%), 2 (28.57%) and 2 (28.57%) farms were categorized as Class II, III, IV and V, respectively. Meanwhile, all the wastewater samples analyzed in this study were classified as Class V. This study provides preliminary data on the quality of drinking and wastewater in select dairy cattle farms in Malaysia. The obtained findings indicate that the quality of drinking water in most of the cattle farms is below the National Water Quality Standards.